2018
DOI: 10.18805/lr-3851
|View full text |Cite
|
Sign up to set email alerts
|

Improving productivity of groundnut (Arachis hypogaea L.) under drip and micro sprinkler fertigation system

Abstract: A field investigation was carried out in farmer's field at Pudhupalayam, TNAU, Coimbatore, during 2015, to improve the productivity of groundnut variety TMV 13 under drip and micro sprinkler fertigation system. The experiment was laid out in randomized block design (RBD) with three replications comprising of 11 treatments. Results indicated that maximum pod yield (3495 kg ha -1 ), haulm yield (6452 kg ha -1 ), harvest index (0.351) and shelling per cent (73.95 per cent) were obtained with drip irrigation at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Soni et al's (2015) experiment was conducted with a randomized block design including 11 treatments. e results have shown that the water-saving rates of drip irrigation at 100% and 75% PE are 40.08% and 55.06%, respectively [4]. Naderianfar et al experiments were carried out at the meteorological station of the Faculty of Agriculture, Ferdowsi University, Mashhad, using a line-source sprinkler irrigation system based on the single-sprinkler installation method [5].…”
Section: Introductionmentioning
confidence: 99%
“…Soni et al's (2015) experiment was conducted with a randomized block design including 11 treatments. e results have shown that the water-saving rates of drip irrigation at 100% and 75% PE are 40.08% and 55.06%, respectively [4]. Naderianfar et al experiments were carried out at the meteorological station of the Faculty of Agriculture, Ferdowsi University, Mashhad, using a line-source sprinkler irrigation system based on the single-sprinkler installation method [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that DF can achieve the combined goals of reducing water usage, increasing N use efficiency, and obtaining high yields. DF can significantly increase crop yields by 10–22% compared with traditional irrigation and fertilization practices [ 23 , 24 , 25 ]. Lu et al [ 14 ] found that compared with FB, DF increased the wheat yield, water productivity, N fertilizer use efficiency, and net income by 43–56%, 44–54%, 47–111%, and 88–100% compared with FB, respectively.…”
Section: Introductionmentioning
confidence: 99%